Recent Approaches on Signal Transduction and Transmission in Acupuncture: A Biophysical Overview for Medical Sciences - Lígia Rebelo Gomes; Pedro Leão (Medical Association of Pharmacopuncture Institute, 2020)
Acupuncture is one of the areas among the alternative therapies that arise high curiosity in the biomedical scientific community. It is particularly popular for treatment of chronic diseases and addictions. However, contrasting with its evidence-based effectiveness, the lack of reasonable explanations for its mode of action divides that scientific community. Difficulties also arise to those responsible for providing information for clinicians and professionals who wish to acquire competencies leading to the acupuncture practice and have a background based on biochemistry and physiology. The classic theories of nerve conduction do not fully explain how information is read and transmitted during the acupuncture treatment. Other theories have been proposed, but they are based on concepts such as biophotonic waves and quantum biochemistry that are difficult to read and understand by those who do not have knowledge in physics. It is the main objective of this review to provide a summary of the main theories and explanatory approaches to the signal transduction and conduction in acupuncture and to describe them in terms of their explanatory hypotheses, limitations, and weaknesses.The most of the literature found support theories for neural conduction, including gate control. They explain the effects of acupuncture in pain relief; few studies have been conducted concerning the conduction based on biophotons. The primo vascular system has been referred as a possible anatomic support for conduction of information during an acupuncture treatment, which could be connected to biophoton transmission. Keywords: acupuncture, biophotons, gate control, neural conduction, primo vascular system